OVERESTIMATION OF BENEFITS OF CANAL IRRIGATION PROJECTS: DECLINE OF PERFORMANCE OVER TIME CAUSED BY DETERIORATION OF CONCRETE CANAL LINING†. (17th April 2019) - Plusquellec, Hervé
Abstract: The paper starts with a review of the findings and recommendations of the evaluation studies at completion of the projects financed by the World Bank up to the mid‐2000s and a review of the performance of a cohort of canal projects by independent consultants and by the FAO using the rapid appraisal process methodology. All the evaluation studies confirmed that the assumptions made at appraisal were overly optimistic: crop yields, cropping intensities, overall irrigation efficiencies and economic evaluations. Not only were the efficiency values quite often largely overestimated, but many economic evaluations assumed that the overall water efficiency values would remain constant over the life of the project. There is strong evidence that hard surface linings could deteriorate within a few years and then seepage returns to that from an unlined canal. Despite the accumulated evidence of the short life of the conventional rigid lining techniques in many irrigation systems, adoption of sustainable options using long‐life geomembranes in irrigation canal lining is still very slow. The paper ends with a short discussion of that technique, which has pervaded all civil engineering disciplines except irrigation. © 2019 John Wiley & Sons, Ltd. Résumé: L'article commence par une revue des conclusions et recommandations formulées par les études d'évaluation de projets financés par la Banque Mondiale jusqu'au début des années 2000, puis d'études de la performance d'une cohorte de projets de canaux par des consultants indépendants et par la FAO en utilisant la méthode d'Evaluation Rapide. Toutes ces études de post‐évaluation confirment que les hypothèses adoptées lors de la préparation de ces projets étaient trop optimistes: rendements des cultures, intensités culturales, efficiences hydrauliques et évaluations économiques. Non seulement les efficiences sont souvent largement surestimées, mais beaucoup d'évaluations économiques supposent que les valeurs d'efficience globale de l'eau demeureront constantes pendant toute la durée du projet. Or il est maintenant bien connu que les revêtements rigides peuvent se détériorer dans les années suivant la construction jusqu'au point où les pertes seront proches d'un canal non revêtu. Malgré l'évidence de la courte durée des revêtements rigides dans de nombreux systèmes d'irrigation, l'adoption de solutions plus durables à l'aide de géomembranes est encore très lente. L'article se termine par une brève discussion de ces techniques qui ont largement pénétré tous les secteurs du Génie Civil sauf celui de l'irrigation. © 2019 John Wiley & Sons, Ltd.